Gadolinium‐ethoxybenzyl‐diethylenetriamine pentaacetic acid‐enhanced magnetic resonance imaging as a useful detection method for advanced primary biliary cirrhosis. Issue 10 (2nd March 2015) - Takeyama, Yasuaki; Tsuchiya, Naoaki; Kunimoto, Hideo; Fukunaga, Atsushi; Sakurai, Kunitoshi; Hirano, Genryu; Yokoyama, Keiji; Morihara, Daisuke; Anan, Akira; Irie, Makoto; Shakado, Satoshi; Sohda, Tetsuro; et al.
Abstract : Aim: In primary biliary cirrhosis (PBC), damaged hepatocytes resulting from chronic cholestasis follow a compensatory mechanism that alters hepatobiliary transporter expression to reduce the accumulation of potentially toxic compounds such as bile acid. Organic anion transporter peptide 1B3 (OATP1B3), which transports agents such as gadolinium‐ethoxybenzyl‐diethylenetriamine pentaacetic acid (Gd‐EOB‐DTPA), has reduced expression in the late stages of PBC. Therefore, we investigated the use of Gd‐EOB‐DTPA‐enhanced magnetic resonance imaging (MRI) as a useful detection method for the advanced staging of PBC. Methods: Stage I−III PBC (non‐liver cirrhosis [LC]‐PBC, n  = 12), stage IV (LC‐PBC, n  = 6), and non−PBC patients (control group, n  = 4) were included in this study. We obtained liver tissue samples by percutaneous liver biopsy. Hepatic OATP1B3 expression was determined immunohistochemically, and OATP1B3 mRNA levels were assessed using real‐time reverse transcription polymerase chain reaction. The relative enhancement (RE) in the hepatobiliary phase was calculated using the signal intensity of Gd‐EOB‐DTPA‐enhanced MRI. Results: Immunohistochemistry revealed markedly reduced expression of OATP1B3 in hepatocytes around the central vein in LC‐PBC patients. Hepatic OATP1B3 mRNA expression in LC‐PBC patients was significantly lower than that in non‐LC‐PBC patients ( P  < 0.05). The RE on MRI was significantly decreased in the LC‐PBC group (0.33 ± 0.14) compared with the non‐LC‐PBC (0.91 ± 0.15, P  < 0.01) and control (0.92 ± 0.20, P  < 0.01) groups. Conclusion: Gd‐EOB‐DTPA‐enhanced MRI may provide a useful detection method for liver disease in patients with LC‐PBC.